Oceanographic Data of the 51st Japanese Antarctic Research Expedition from December 2009 to March 2010 - IZUMI, Noriaki (国立極地研究所, 2016)
Table 1 | http://polaris.nipr.ac.jp/~parc/pub/v027/nipr_parc_200_0001.xlsx Table 2 | http://polaris.nipr.ac.jp/~parc/pub/v027/nipr_parc_200_0002.docx departmental bulletin paper